Method for improving performance of perovskite solar cell through hole transport layer bonding site design
The transparent electrode indium tin oxide was treated by solution hydroxylation to construct dense and stable hydroxyl groups and oxygen vacancies, which solved the problem of insufficient bond density and stability of self-assembled monolayer molecules, and significantly improved the photovoltaic performance of perovskite solar cells.
Patent Information
- Application Number
- CN202411869594.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-18
- Publication Date
- 2025-03-14
- Estimated Expiration
- 2044-12-18
AI Technical Summary
In existing perovskite solar cells, the bond density and stability of self-assembled monolayer molecules are insufficient, resulting in low photogenerated carrier extraction efficiency and attenuation of photovoltaic performance.
The transparent electrode indium tin oxide is treated by solution hydroxylation to construct dense and stable hydroxyl groups and oxygen vacancies as bonding sites for self-organized monolayers, thereby improving the bonding density and stability of self-assembled monolayer molecules.
It significantly improves the bonding density and stability of self-assembled monolayer molecules, improves the photovoltaic performance of perovskite solar cells, including improving the filling factor and short-circuit current density, and simplifies the preparation process and shortens the time cost.
Smart Images

Figure FT_1 
Figure FT_2 
Figure FT_3
Abstract
Description
Technical Field
[0001] The invention relates to a method for improving the performance of a perovskite solar cell by designing a bonding site of a hole transport layer, and belongs to the technical field of semiconductor optoelectronic devices and solar cells. Background Art
[0002] Perovskite solar cells have great development potential as a new type of solar cell. Currently, the most efficient perovskite solar cells are mainly based on Figure 1 The structure shown in the figure, in which the hole transport layer is a self-assembled monolayer molecule (such as MeO-2PACz, MeO-4PACz, Me-2PACz, Me-4PACz, etc.). The self-assembled monolayer molecule is very thin, only about 5nm thick, and is bonded to a transparent electrode (such as indium tin oxide ITO, fluorine-doped tin oxide FTO) to play the role of extracting photogenerated holes. Its bonding density directly determines whether it can effectively extract holes. In addition, if the distribution of the self-assembled monolayer molecules is not dense enough, it will also cause the upper perovskite layer and the lower ITO layer to directly contact, which will also cause the photogenerated carriers generated in the perovskite layer to be quenched. At the same time, the bonding stability of the self-assembled monolayer molecule is also very important. If it is desorbed from ITO, it will directly lead to the attenuation of the photovoltaic performance of the device. Therefore, improving the bonding density and stability of the self-assembled monolayer molecule is crucial to the photovoltaic performance of perovskite solar cells.
[0003] Typically, the assembly of a single molecule (for example, MeO-2PACz) Figure 2 The PO bonds on the ITO surface are bonded to the ITO surface by condensation reaction with the hydroxyl (OH) groups on the ITO surface (Figure A in the middle) Figure 2 B and D in the figure). Therefore, as a bonding site, the density of the hydroxyl groups on ITO determines the distribution density of the self-assembled monolayer. The stability of the hydroxyl groups on ITO also affects the stability of the self-assembled monolayer. Constructing rich, dense and stable hydroxyl groups on ITO is a prerequisite for obtaining a high-quality self-assembled monolayer. In addition, the self-assembled monomolecule is mainly bonded by the condensation reaction between the PO bond and the hydroxyl group on the surface of ITO, and the bonding method is relatively simple. Therefore, the present invention is proposed. Summary of the invention
[0004] The purpose of the present invention is to provide a method for designing bonding sites of a hole transport layer to improve the performance of perovskite solar cells, specifically based on a solution-based hydroxylation treatment of transparent electrode indium tin oxide, to construct dense and stable hydroxyl groups and a large number of oxygen vacancies on its surface as bonding sites for subsequent self-organized monolayers, thereby improving the bonding density and stability of the self-assembled monolayer molecules thereon, and improving the photovoltaic performance of perovskite solar cells.
[0005] The hydroxylation etching method of transparent electrode indium tin oxide provided by the present invention comprises the following steps: Immersing ITO in a hydroxylation etching solution, and performing hydroxylation treatment under immersion or heating ultrasound; The hydroxylation etching solution is a mixture of sulfuric acid, hydrogen peroxide and water.
[0006] The present invention adopts a solution with hydroxylation ability to directly immerse or ultrasonically treat commercial ITO, and the hydroxylation etching reaction formula is:
[0007]
[0008]
[0009]
[0010] Since the surface of commercial ITO contains organic pollutants, it needs to be cleaned before use. The commonly used methods in this field are to use detergents, deionized water, acetone and isopropanol to ultrasonically treat ITO, ultraviolet ozone treatment or oxygen plasma treatment to remove surface organic matter. The hydroxylation solution used in the present invention itself has a strong oxidizing property, so it can naturally remove surface organic matter through oxidation and dehydration during the hydroxylation treatment. That is, commercial ITO can be used directly after being hydroxylated in one step by the present invention, and the traditional multi-step ITO pretreatment is omitted, which greatly simplifies the preparation steps of perovskite solar cells and shortens the time cost. Fig.12 shown.
[0011] Preferably, in the hydroxylation etching solution, the volume ratio of the sulfuric acid, the hydrogen peroxide and the water is 4-7:2-3:1-2, preferably 7:3:2.
[0012] Preferably, the mass concentration of the sulfuric acid is 80-98%, and the mass concentration of the hydrogen peroxide is 20-40%.
[0013] The hydroxylation solution can fully hydroxylate the ITO surface by soaking ITO in it for as fast as 15 seconds, changing its surface from hydrophobic to hydrophilic. This ultrafast hydroxylation can greatly shorten the preparation time of perovskite solar cells. The hydroxylated ITO surface has abundant hydroxyl groups, which makes the subsequent self-assembled monolayer bonded more densely.
[0014] Preferably, the soaking conditions are as follows: The temperature is 60-90℃ and the time is not less than 15s.
[0015] Since the ITO surface itself does not contain hydroxyl groups, the ITO hydroxylation used in the art is usually ultraviolet ozone treatment or oxygen plasma treatment. However, the gas treatment method is not sufficient for the hydroxylation of the ITO surface, that is, the ITO surface does not form a very dense hydroxyl distribution. In addition, the traditional hydroxylation method will also introduce some unstable hydroxyl groups through physical adsorption. The hydroxylation method of the present invention can directly immerse ITO in a hydroxylation solution. Compared with the traditional hydroxylation method, the method of the present invention can fully hydroxylate ITO, and the hydroxyl groups introduced on the ITO surface by the present invention are very stable, which is conducive to the subsequent dense and stable self-assembled monomolecular bonding.
[0016] Preferably, the conditions of the thermal ultrasound are as follows: The temperature is 60-120℃ and the time is 10-35min.
[0017] By heating the hydroxylation solution and ultrasonically treating it, abundant oxygen vacancies will be formed on the ITO surface. In the ITO lattice, since O and In are bonded, oxygen vacancies are equivalent to uncoordinated indium. Therefore, it is equivalent to constructing abundant uncoordinated indium ions. Since the O atom on the P=O bond on the self-assembled single molecule has a lone pair of electrons, it can form a coordination bond with the uncoordinated indium ion ( Figure 2 C in the middle). That is, in the hydroxylation process, the present invention not only forms a large number of stable hydroxyl groups on the ITO surface for subsequent self-assembled single molecules to bond with, but also constructs abundant uncoordinated indium for subsequent self-assembled single molecules to bond with P=O bonds, creating a new bonding mode and thus providing more bonding sites. The present invention can change the bonding of self-assembled single molecules on ITO from traditional monodentate to bidentate, and can further promote the subsequent self-assembled single molecules to bond more densely and stably.
[0018] Since the hydroxylation solution used in the present invention is highly corrosive, the weak crystalline phase on the surface of ITO will be etched and removed during the hydroxylation process by heating and ultrasonic treatment, which can improve the conductive uniformity of ITO and thus improve the fill factor of the final perovskite solar cell.
[0019] Since the hydroxylation solution used in the present invention is highly corrosive, it can also form a nanostructured light anti-reflection structure on the ITO surface through heating and ultrasonic treatment, which can significantly improve the transmittance of light, thereby allowing more sunlight to pass through ITO and reach the perovskite layer, thereby increasing the short-circuit current of the final perovskite solar cell.
[0020] The hydroxylated indium tin oxide electrode obtained by the method of the present invention also belongs to the protection scope of the present invention.
[0021] On the basis of the hydroxylated indium tin oxide electrode, the present invention also provides a perovskite solar cell device, the substrate of which is the transparent electrode indium tin oxide; The self-assembled monolayer bonded on the transparent electrode indium tin oxide serves as a hole transport layer.
[0022] The present invention is based on the solution method to hydroxylate the transparent electrode surface, and construct a large number of stable hydroxyl groups on its surface as bonding sites for subsequent self-assembled monolayers, thereby improving the bonding density and stability of the self-assembled monolayer. Secondly, the method of the present invention can also construct a large amount of uncoordinated indium on the ITO surface, so that the self-assembled monolayer molecules can also bond to the ITO surface through P=O bonds, creating a new bonding method. The self-assembled monolayer constructed based on the method of the present invention is used as a hole transport layer to obtain a perovskite solar cell with higher efficiency and stability.
[0023] The method of the present invention can also spontaneously form a nano anti-reflection structure on the surface of ITO, which can greatly increase the photon transmission and thus improve the short-circuit current density of the perovskite solar cell. In addition, in the traditional method, commercial ITO requires multiple time-consuming pretreatments by default before use, while the present invention allows commercial ITO to be used directly after only one step of treatment designed by the present invention, greatly saving the time and economic costs of device preparation, which is of great significance to promoting the industrial development of perovskite solar cells. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 Schematic diagram of the structure of a perovskite solar cell device.
[0025] Figure 2 Schematic diagram of the self-assembled molecules and how they bond to ITO.
[0026] Figure 3 This is the XPS test result of ITO after treatment with different hydroxylation etching times.
[0027] Figure 4 These are the water contact angle test results of ITO before and after hydroxylation etching. Figure 5 These are photos of the water dripping experiment on ITO before and after hydroxylation etching.
[0028] Figure 6 The water contact angle test results of ITO at different immersion times.
[0029] Figure 7 The time-of-flight secondary ion mass spectrometer test results are for samples after preparing a self-assembled monolayer on ITO treated by conventional hydroxylation and hydroxylation by the method of the present invention.
[0030] Figure 8The conductive atomic force microscope test results of the samples after preparing the self-assembled monolayer on ITO treated by the traditional method and the method of the present invention are shown.
[0031] Fig. 9 The surface potential test results of the samples before and after aging at 85° C. for 600 hours after preparing the self-assembled monolayer on ITO treated by conventional hydroxylation and hydroxylation according to the method designed by the present invention.
[0032] Fig.10 Atomic force microscopy test results of ITO surface after different hydroxylation etching times.
[0033] Fig.11 This is the light transmittance curve of ITO after different hydroxylation etching times.
[0034] Fig.12 Schematic diagram of ITO pretreatment in a traditional manner and ITO pretreatment using the method of the present invention.
[0035] Fig.13 The current-voltage scanning curves of the perovskite solar cell prepared on ITO pretreated in a traditional manner and ITO pretreated by the method of the present invention.
[0036] Fig.14 These are the stability test results of perovskite solar cells prepared on ITO pretreated in a traditional manner and ITO pretreated by the method of the present invention. DETAILED DESCRIPTION
[0037] The present invention will be further described below in conjunction with specific embodiments, but the present invention is not limited to the following embodiments.
[0038] The methods are conventional methods unless otherwise specified. The raw materials can be obtained from public commercial channels unless otherwise specified.
[0039] Example 1: Hydroxylation of ITO substrate 1) Preparation of hydroxylation solution: Pour 700 ml of sulfuric acid (98%) into a beaker, slowly pour in 300 ml of hydrogen peroxide (30%) while stirring, and continue to add 200 ml of deionized water while stirring.
[0040] 2) Rapid hydroxylation of ITO: Soak commercial ITO directly in the hydroxylation solution (temperature is 80°C) for 15 seconds and then take it out. Rinse the residual hydroxylation solution on the surface with deionized water and blow dry the ITO with a nitrogen gun. It can be used directly without any further treatment.
[0041] 3) ITO hydroxylation etching: Heat the hydroxylation solution to 60°C, directly immerse the commercial ITO in the hydroxylation solution and ultrasonicate at 60°C for 25 minutes, then take out the ITO and rinse the residual hydroxylation solution on the surface with deionized water, blow dry the ITO with a nitrogen gun and use it directly without any further treatment.
[0042] A self-assembled monolayer is prepared on the ITO substrate obtained by the above method as a hole transport layer, and conventional perovskite solar cell preparation is subsequently completed.
[0043] The subsequent preparation method of the perovskite solar cell device is as follows: 1. Preparation of self-assembled monolayer: Taking MeO-2PACz as an example, the self-assembled monolayer was prepared at 0.5 mg / ml in anhydrous ethanol, and spin-coated on an ITO substrate at 3000 rpm for 30 seconds in a glove box, followed by annealing on a hot plate at 100°C for 10 minutes.
[0044] 2. Preparation of perovskite layer: The component of perovskite is Rb 0.05 Cs 0.05 MA 0.05 FA 0.85 Pb(I 0.95 Br 0.05 )3, whose precursor is made by dissolving RbI:15.9 mg, CsI:19.3 mg, PbBr2:27 mg, MABr:9.4 mg, FAI:219.3 mg and PbI2:657 mg in 1 ml DMF:DMSO (v:v=4:1) mixed solvent. The spin coating of the perovskite precursor is divided into two consecutive steps, spin coating at 1000 rpm for 10 seconds, and then spin coating at 4000 rpm for 35 seconds. The first step is to spread the solution, and the second step is high-speed rotation to make it more evenly spread. At 25 seconds in the second step, 150 μl of chlorobenzene is added to the precursor film as an anti-solvent. The film is then annealed at 100°C for 10 minutes.
[0045] 3. Preparation of electron transport layer and barrier layer: Spin coat PCBM dissolved in chlorobenzene with a concentration of 20 mg / ml at 1500 rpm for 30 seconds, and then anneal at 100°C for 10 minutes as an electron transport layer. Then spin coat BCP dissolved in isopropanol with a concentration of 0.5 mg / ml on PCBM at 5000 rpm for 30 seconds as a barrier layer.
[0046] 4. Preparation of silver electrode: Silver electrode with a thickness of about 80 nanometers was prepared on the above film by thermal evaporation.
[0047] Figure 3This is the XPS test result of ITO after treatment with different hydroxylation etching times. It can be found that with the extension of treatment time, the surface hydroxyl groups gradually increase.
[0048] Figure 4 To measure the water contact angle of ITO before and after treatment, hydroxyl group, as the most typical hydrophilic group, can directly reflect the number of hydroxyl groups on the surface through the water contact angle. The better the hydrophilicity, the smaller the water contact angle, and the more hydroxyl groups on the surface.
[0049] Figure 5 The following are photos of the water drop experiment of ITO before and after treatment. It can be seen that the water droplets spread directly on the treated ITO surface, proving that it has good water wettability, thus confirming that the ITO surface has abundant hydroxyl groups.
[0050] Figure 6 The water contact angle test results of ITO at different immersion times. In the present invention, the hydroxylation of ITO can be completed in 15 seconds at the fastest. As can be seen from the figure, as the immersion time increases, the water contact angle gradually decreases, reaching 6 degrees at 15 seconds, confirming that abundant hydroxyl groups have been constructed on the ITO surface.
[0051] Figure 7 The results of time-of-flight secondary ion mass spectrometry (TOF-SIMS) tests of samples after preparing self-assembled monolayers on ITO treated by conventional hydroxylation and hydroxylation by the method of the present invention. The samples after preparing self-assembled monolayers on ITO treated by conventional hydroxylation and hydroxylation by the method of the present invention were then tested by TOF-SIMS. The distribution of the self-assembled monolayer can be reflected by observing the distribution of PO3 groups. It can be found that the self-assembled monolayer prepared on ITO treated by hydroxylation by the method of the present invention is more densely distributed because there are more bonding sites.
[0052] Figure 8 The conductive atomic force microscope test results are shown in Figure 2. The samples after preparing the self-assembled monolayer on the ITO treated by the traditional method and the method of the present invention are subjected to the conductive atomic force microscope test. Since the ITO of the lower layer has a conductivity two orders of magnitude higher than the self-assembled monolayer, if the self-organized monolayer coverage is not dense, the probe will directly contact the ITO below during the test, resulting in a point where the current surges. The coverage density of the self-assembled monolayer can be judged by the point where the current surges. It can be found that the self-assembled monolayer prepared on the ITO treated by the method of the present invention has a denser coverage.
[0053] Fig. 9The surface potential test results before and after aging at 85°C for 600 hours. After preparing a self-assembled monolayer on ITO treated by conventional hydroxylation and hydroxylation by the method of the present invention, the surface potential test results of the samples were tested before and after aging at 85°C for 600 hours. It can be found that the self-assembled monolayer prepared on the hydroxylated sample prepared by the present invention has very excellent stability.
[0054] Fig.10 The atomic force microscopy test results of the ITO surface after different hydroxylation etching times show that its surface gradually becomes rough and gradually forms pyramid-like structures, which help reduce light reflection losses.
[0055] Fig.11 The light transmittance curves of ITO after treatment with different hydroxylation etching times show that the best light transmittance is achieved at 25 minutes.
[0056] Fig.12 Schematic diagram of ITO pretreatment using the traditional method and the method designed by the present invention.
[0057] Fig.13 The current-voltage scanning curves of the perovskite solar cells prepared on the ITO pretreated by the traditional method and the ITO pretreated by the method of the present invention show that the present invention can improve the efficiency of the perovskite solar cell to 26.3%.
[0058] Fig.14 The stability of perovskite solar cells prepared on ITO pretreated in a traditional manner and ITO pretreated by the method of the present invention was tested. It can be found that under various aging conditions, the perovskite solar cells prepared on ITO pretreated by the method of the present invention have higher stability.
Claims
1. A method for hydroxylating and etching transparent electrode indium tin oxide, comprising the following steps: Immersing ITO in a hydroxylation etching solution, and performing hydroxylation treatment under immersion or heating ultrasound; The hydroxylation etching solution is a mixture of sulfuric acid, hydrogen peroxide and water.
2. The hydroxylation etching method according to claim 1, characterized in that: In the hydroxylation etching solution, the volume ratio of the sulfuric acid, the hydrogen peroxide and the water is 4-7:2-3:1-2.
3. The hydroxylation etching method according to claim 1 or 2, characterized in that: The mass concentration of the sulfuric acid is 80-98%, and the mass concentration of the hydrogen peroxide is 20-40%.
4. The hydroxylation etching method according to any one of claims 1 to 3, characterized in that: The soaking conditions are as follows: The temperature is 60-90℃ and the time is not less than 15s.
5. The hydroxylation etching method according to any one of claims 1 to 3, characterized in that: The conditions of the thermal ultrasound are as follows: The temperature is 60-120℃ and the time is 10-35min.
6. The transparent electrode indium tin oxide obtained by the hydroxylation etching method according to any one of claims 1 to 5.
7. Use of the transparent electrode indium tin oxide according to claim 6 in the preparation of perovskite solar cell devices.
8. A perovskite solar cell device, the substrate of which is the transparent electrode indium tin oxide according to claim 6; The self-assembled monolayer bonded on the transparent electrode indium tin oxide serves as a hole transport layer.
Citation Information
Patent Citations
Organic solar cell based on polyfluorene cathode interface self-assembly anode plasma resonance effect and preparation method of organic solar cell
CN105470396A
Preparation of perovskite solar cell based on self-assembly micromolecule one-step spin coating
CN116193942A
Method for improving wettability of perovskite solar cell substrate electrode, perovskite solar cell and preparation method thereof
CN118354650A
Surface modified ITO glass and producing method thereof
KR1020070023504A